Prolonged cholestasis induced by endoscopic retrograde cholangiopancreatography. Issue 2 (14th May 2010) - Patani, Olomuza; Foulkes, Sian L; Njie, Ramatoulie; Aspinall, Richard J
Abstract : The case of a 54-year-old woman who presented with choledocholithiasis and underwent successful endoscopic stone extraction to clear the common bile duct is described. However, her jaundice and liver biochemistry continued to deteriorate despite repeat endoscopic retrograde cholangiopancreatography (ERCP), with further imaging confirming a patent biliary tree. The clinical, radiological and pathological features were in keeping with prolonged cholestasis as a complication of ERCP. The pathophysiology of this unusual syndrome and the therapeutic options available are discussed.